Web-Based Academic Information System Design Plan for Kindergarten - Fithrie Soufitri; Fani Syahrina Lubis; Aulia Rahmah Lubis (PT Inovasi Pratama Internasional, 2022)
Website is one of the services that can be used by computer users connected to the internet . The website makes it easy for computer users to interact with other internet users and browse information on the internet network . Kindergarten is one of the institutions engaged in the field of education for early childhood. The purpose of making this thesis is to create an academic information website for parents of students in kindergarten. To create a kindergarten website , several methods are needed. In this thesis report the methods used include literature study, observation and interviews. This website was developed using the PHP programming language and database used is a MySQL database. In this thesis report, a system has been created that has facilities such as student data, teacher data, class data, child achievement data, child grade data, child report cards data, announcement data, and activities in kindergarten.